Energy materiality: A conceptual review of multi-disciplinary approaches. (October 2019) - Balmaceda, Margarita; Högselius, Per; Johnson, Corey; Pleines, Heiko; Rogers, Douglas; Tynkkynen, Veli-Pekka
Abstract: This jointly authored essay reviews recent scholarship in the social sciences, broadly understood, that focuses on the materiality of energy. Although this work is extraordinarily diverse in its disciplinary and interdisciplinary influences and its theoretical and methodological commitments, we discern four areas of convergence and divergence that we term the locations, uses, relationalities, and analytical roles of energy materiality. We trace these convergences and divergences through five recent scholarly conversations: materiality as a constraint on actors' behavior; historical energy systems; mobility, space and scale; discourse and power via energy materialities; and energy becoming material.